Complexes of multifunctional phosphorus ligands. Rhenium(V) complexes of the multidentate phenoxyphosphine ligands bis(o-trimethylsilyloxyphenyl)phenylphosphine and tris(o-trimethylsilyloxyphenyl)phosphine. Stepwise elimination of Me3SiX (X = Cl, OEt) from the metal-ligand system - Cavell, Ronald G.; Hilts, Robert; Luo, Hongyan; McDonald, Robert (My University, 1998)
The silylated aryloxo ligands bis(o-silyloxyphenyl)phenylphosphine (abbreviated PhP{OT}2) and tris(o-trimethylsilyloxyphenyl)phosphine (abbreviated P{OT}3, where T = Me3Si) were prepared. Complexation reactions with OReCl2(OEt)(PPh3)2 and OReCl3(PPh3)2 proceed by displacement of one PPh3 and the subsequent stepwise replacement of the OEt and/or Cl substituents. The new complex Re(O)Cl2[κ2-(P,O)-(PhP{O}{OT})](PPh3), formed by elimination of Me3SiOEt, exists in diastereomeric cis and trans forms. Elimination of a second equivalent of Me3SiCl gives Re(O)Cl[κ3-(P,O,O)-(PhP{O}2)](PPh3). Similarly P{OT}3 converts Re(O)Cl2(OEt)(PPh3)2 to ReOCl2[κ2-(P,O)-(P{O}{OT}2)](PPh3) (5) (structurally characterized as 5·0.875CH2Cl2): crystal data; triclinic P1̄, a = 14.302(4) Å, b = 18.734(2) Å, c = 17.639(4) Å, α = 80.950(12)°, β = 80.12(2)°, γ = 81.76(2)°, Z = 4. Final R1 and wR2 values are 0.0852 and 0.1525, respectively on Fo2 > 2σ(Fo2) data (or 0.1948 and 0.2019 on all data). The phenoxy phosphine ligand in 5 is bound via P and one O to Re. The P atoms are mutually cis to each other and to the terminal oxygen on Re. Two ortho-trimethylsiloxy substituted phenyl rings dangle from the coordinated phosphorus atom. Complex 5 can be converted to Re(O)Cl[κ3-(P,O,O)-(P{O}2{OT})](PPh3) (6) by treatment with PPN+ Cl- and 6 was also obtained by direct reaction of Re(O)Cl3(PPh3)2 with P{OT}3 at higher temperatures. The complex 6 has been structurally characterized: crystal data triclinic, P1̄, a = 10.1509(6) Å, b = 12.1123(8) Å, c = 16.2142(14) Å, α = 97.851(7)°, β = 94.852(7)°, γ = 96.889(6)°, Z = 2. Final R1 and wR2 values were 0.0303 and 0.0721 on Fo2 > 2σ(Fo2) data (or 0.0348 and 0.0742 on all data). The phenoxyphosphine ligand in 6 is bound facially to Re through P and two of the phenoxy oxygens. The Ph3P group and terminal oxygen atoms are cis to the oxygen atoms of the phenoxy ligands and the Cl lies trans to P. One trimethylsiloxyphenol group dangles. Careful hydrolysis of 6 gave Re(O)Cl[κ3-(P,O,O)-(P{O}2{OH})](PPh3) which was also formed during complexation reactions in moist solvent. Solution 31P{1H} NMR demonstrated cis- or trans-(P,P) geometry for the complexes, which was confirmed in the two aforementioned cases by structure determinations.
Keywords: monooxidized bis(phosphino)amines; structural characterization; platinum(II) complexes; rhodium(l) complex; stereochemistry